Chemical submission: an in-depth analysis of its impact on crimes against sexual freedom - Alonso, Daniel Suárez (International e-journal of criminal sciences, 2024)
Chemical submission has become a matter of interest in crimes against sexual freedom in recent years. This paper aims to reduce and prevent this type of crime. It will address the element of chemical submission within the crimes of sexual freedom, the analysis of the problem of sexual assaults, highlighting the type of substance and the most used psychoactive groups and all this analyzing the most important changes introduced by the new Organic Law 10/2022, of September 6, of integral guarantee of sexual freedom and its current modification. And an action procedure for the prevention of this type of crime will be established. A bibliographic review will be carried out by means of the PRISMA methodology for systematic reviews of the last year. The results obtained will highlight the most commonly used drug, the victim, the aggressor and the need for action protocols. In the future, the research should be based on real databases, expanding and updating the information, in order to be able to make more effective action guidelines, being able to inform and raise awareness in society about this type of crime.